Ang Gamit ng Filipino sa mga Talakayan sa Klasrum sa Universit of Hawaii / The Use of Filipino in Classroom Interactions at the University of Hawaii. - Pagkalinawan, Leticia (Malay, 2015)
This paper presents a descriptive analysis o the use of Filipino as a language of discourse in the advanced level. Specifically, it examines the language patterns and the functions of language in classroom discussions. Understanding the use of language in teaching and learning will provide teachers with a heightened awareness of classroom discourse that will lead to advanced language learning. The data of this study consist of field notes, and transcripts of audio-recordings of student talk collected during classroom discussions. Findings of the study show that classroom interactions are mostly teacher-controlled and generally reflect low level interaction. Students' verbal responses are limited to word and/or phrase only and the use of code-mixing and code-switching is being tolerated. However, classroom interactions are generally encouraging, welcoming, supporting and non-threatening.